Diagnostic Efficacy of Aldehyde Test in Late Cases of Kala-Azar - Parvin, R; Rahman, ME; Islam, MN; Uddin, SN; Khaleque, MA; Choudhury, AM (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2007 Jul;16(2): 160-164 The abstract of this article is available on the PubMed website